Four Korean teacher learners' academic experiences in an Australian TESOL programme and disclosure of their multiple identities. Issue 1 (3rd May 2016) - Han, Insuk
Abstract : Purpose: The purpose of this paper is to explore four Korean teacher learners' academic experiences in an Australian Teaching English to Speakers of Other Languages (TESOL) master's programme. By investigating the ways they encounter the overseas teacher education programme and how to interact with different meanings, this study reveals Korean teacher learners' multiple selves and several meaning systems embedded in them. The understandings from the case provide some implications for curriculum internationalisation in higher education as well as TESOL. Design/methodology/approach: Interviews, a focus group discussion and metaphors were used as data, and from these narratives, the participants' experience was categorised into the programme's aspects of the methods, contents and applicability, materials and usefulness, assessment criteria and feedback and communication and support. Each interview was undertaken in a library for around one and a half hours. At the end of the interviews, participants were required to produce a metaphor of desirable teacher/lecturer roles. For triangulation, a focus group discussion was conducted for approximately two hours, in which three participants could represent social worlds, evaluate them and establish themselves as members of particular groups. All the questions were semi-structured and about teaching and learning experiences in Korea and Australia and ideas of lecturers' roles, practices and desirable pedagogy. Findings: From the analysis of the participants' experiences in these, it was revealed that their identity was tangled with that of the (English) teacher, consumer, (international) student and non-native speaker. The meaning systems of these identities were based on the mixture of the Korean traditional and Western or modern educational values: positive attitude towards communicative language teaching and its contexutalisation, pursuit of practical knowledge and pragmatic ideas, favour for discussions and getting confirmation from authorities and being positioned in the weak and using different communication rules, etc. Research limitations/implications: From the insights from this case, the lecturers and programme coordinators in intercultural TESOL courses will gain some ideas for a curriculum responsive to international needs. While it cannot be denied that the small scale of the study has limitations for generalisation, this research will be one of the required literatures which examines East Asians or Koreans in Western academic institutions, given that this qualitative study complements the findings of the quantitative studies by specifically disclosing the ways Korean teacher learners' identity and the meaning systems of desirable pedagogies. Practical implications: For the curriculum internationalisation in TESOL and several higher education (HE) courses, the lecturers' and the institutions' awareness of cultural differences and reducing stereotyping, language support and being explicit about new rules in the new game and communication for support and respectful and professional encounters are essential, alongside the learners' voluntary endeavour for academic adaptation in their overseas learning. Social implications: The effort to understand each other in education is a good start for intercultural communication, that is, curriculum internationalisation in TESOL as well as higher education. Originality/value: Different from other studies in similar areas, this study discloses the multiple selves/identities and meaning systems of the teacher learners in TESOL, by maximising the benefits of a qualitative study. The understandings from this approach help the researcher draw out practical implications for curriculum internationalisation in TESOL and HE.